An exploratory study of young EFL learners' aural and written receptive multi-word unit knowledge. (June 2023) - Shin, Dongkwang; Lee, Jang Ho; Choi, Wonkyung
Abstract: While accounting for recent theoretical arguments regarding the modality-specific nature of lexical knowledge, this exploratory study sought to measure young EFL learners' aural receptive multi-word unit (MWU) knowledge and then to compare this to their written counterpart. A total of 120 sixth-grade Korean EFL learners participated in the study, completing aural and written receptive MWU tests that included the identical set of 40 MWUs, which were extracted from the Corpus of Contemporary American English. Both measured participants' meaning-recall knowledge, with the only difference being the mode of target MWU presentation. The results demonstrated that the participants had aural receptive knowledge of about one-third of all MWUs in the first four 500-word levels. They also showed that their aural receptive knowledge of the target MWUs was significantly smaller than their written counterpart. The analysis also indicated that the participants' incorrect recognition of aural forms of some MWUs may partially account for the relatively lower aural test scores. We conclude this paper by highlighting our findings' implications for research and teaching regarding aural MWU knowledge.